Environmental Contaminants in Biota Interpreting Tissue Concentrations, Second Edition - Beyer, W. Nelson; Meador, James P. (Taylor & Francis, 2011)
Discussing the interpretation of tissue concentrations of contaminants in wildlife, this updated edition of a bestseller draws on current scientific research and includes new chapters and greater emphasis on aquatic organisms. Each chapter provides a summary and review of a specific chemical along with direction on research methods and the interpretation of conflicting or insufficient data. Chapters include a comprehensive history of contaminant interpretation in wildlife and fish, the use of tissue residues in ecological risk assessment, and detailed coverage of all bioaccumulative contaminants and their physiologic affects.